VALIDASI SIMULASI TEKANAN DAN SUHU AIR SERTA SUHU DAGING SAPI SELAMA PEMASAKAN DALAM PRESSURE COOKER - Saparudin, Dyah Wulandani, dan Nanik Purwanti (Jurnal Teknologi Industri Pertanian, 2016)
Beef cooked with pressure cooker can produce soft texture in relatively short time. In previous study,polytetrafluoroethylene (PTFE) was used for developing a heat transfermodel in pressure cooker. The aim ofpresent study was to validate previously PTFE heat transfer model with actual beef. To get the simulation withan error rate as small as possible, the modification of the model as well as the as sumptions adjusted inaccordance with the characteristics of beef. Finite difference methods with Euler scheme was used to performthe computation. A commercial pressure cooker of 8 and 10 L in volume were used to validate the model.Cooking time was 60 minutes after releasing steam from pressure cookeroutflow through the pressure valve.Meat used was knuckle section of ongole beef with the age of two to three years.The result showed that thedeveloped model of steam pressure, water and beef temperatures could predict well the real phenomena duringtime process in the pressure cooker. The error of model was estimated with mean absolute percentage errormethods. The error of model of gas pressure in the pressure cooker 10 and 8 L were 7.1% and 3.2%,respectively; water temperaturesof 3.6% and 1.4%, respectively; and the meat mid point temperatures of 2.3%and 4.2%, respectively.Thus, the model could be used to estimate the cooking time and energy needed forcooking time and meat research purposes relating to cooking time and temperature.Keywords: beef, pressure cooker, simulation, temperature